Labor Market Insertion Strategies in the Public Sector: A Study of Untrm Accounting Graduates (2021-2023) - Salazar, Carlos Alberto Hinojosa; Puente, Edward Enrique Rojas de la; Escoba, Benjamín Roldan Polo; Peláez, Heisely Mori; Camacho, Consuelo González; Caballero , Ariadna Martínez (Journal of Ecohumanism, 2024)
This study analyzes the strategies that favor the labor market insertion of Accounting graduates of the Universidad Nacional Toribio Rodríguez de Mendoza (UNTRM) in public entities during the period 2021-2023. A quantitative methodology was used, with a descriptive and correlational design, applying surveys to 81 graduates. The data were processed using SPSS and inferential statistical techniques such as Pearson's correlation coefficient were used. The results revealed that the main obstacles are lack of work experience and insufficient dissemination of opportunities. The most effective strategies were agreements between the university and public entities, although the need to implement internship and mentoring programs is highlighted. The conclusion is that it is essential to strengthen the preparation of graduates in soft and technological skills to improve their insertion in the public sector.